KARAKTERISTIK TEPUNG KULIT KENTANG (Solanum tuberosum) SEBAGAI BAHAN PANGAN SUMBER KALIUM - Ratnayani -; Septiani -; Ahmad Fitra Ritonga; Nur Fahlia (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
Potato peel flour (Solanum tuberosum) is a flour that has a potential to be developed as a food source of potassium. This research was conducted to determine the chemical properties of potato peel flour. Potato peel flour is carried out in several stages: peeling potatoes; soaking in 0.3% sodium bisulfite (NaHSO3) solution for 60, 90 and 120 minutes; drying; milling; and sifting. Parameters observed were water content, ash content, protein, fat, carbohydrates and potassium (K). Potato peel flour with various immersions produced has the characteristics of water content (7.84 – 9.03%), ash content (4.15 – 4.67%), protein (11.35 – 11.60 %), fat ( 0.74 – 0.87%), carbohydrates (74.63 – 75.26%), and potassium (1231.32 – 1671.86 mg/100 g). Based on the potassium content, potato skin flour with the highest potassium content was soaked for 120 minutes.